The Venus nighttime atmosphere as observed by the VIRTIS‐M instrument. Average fields from the complete infrared data set. Issue 4 (17th April 2014) - Grassi, D.; Politi, R.; Ignatiev, N. I.; Plainaki, C.; Lebonnois, S.; Wolkenberg, P.; Montabone, L.; Migliorini, A.; Piccioni, G.; Drossart, P.
Abstract We present and discuss here the average fields of the Venus atmosphere derived from the nighttime observations in the 1960–2350 cm−1 spectral range by the VIRTIS‐M instrument on board the Venus Express satellite. These fields include: (a) the air temperatures in the 1–100 mbar pressure range (~85–65 km above the surface), (b) the altitude of the clouds top, and (c) the average CO mixing ratio. A new retrieval code based on the Bayesian formalism has been developed and validated on simulated observations, to statistically assess the retrieval capabilities of the scheme once applied to the VIRTIS data. The same code has then been used to process the entire VIRTIS‐M data set. Resulting individual retrievals have been binned on the basis of local time and latitude, to create average fields. Air temperature fields confirm the general trends previously reported in Grassi et al. (2010), using a simplified retrieval scheme and a more limited data set. At the lowest altitudes probed by VIRTIS (~65 km), air temperatures are strongly asymmetric around midnight, with a pronounced minima at 3LT, 70°S. Moving to higher levels, the air temperatures first become more uniform in local time (~75 km), then display a colder region on the evening side at the upper boundary of VIRTIS sensitivity range (~80 km). As already shown by Ignatiev et al. (2008) for the dayside, the cloud effective altitude increases monotonically from the south pole to the equator. However, the variations observed in night data are consistent with an overall variation of just 1 km, much smaller than the 4 km reported for the dayside. The cloud altitudes appear slightly higher on the evening side. Both observations are consistent with a less vigorous meridional circulation on the nightside of the planet. Carbon monoxide is not strongly constrained by the VIRTIS‐M data. However, average fields present a clear maximum of 80 ppm around 60°S, well above the retrieval uncertainty. Once the intrinsic low sensitivity of VIRTIS data in the region of cold collar is kept in mind, this datum is consistent with a [CO] enrichment toward the poles driven by meridional circulation.